Supercapacitors: Uniform Hollow Mesoporous Nickel Cobalt Sulfide Microdumbbells: A Competitive Electrode with Exceptional Gravimetric/Volumetric Pseudocapacitance for High‐Energy‐Density Hybrid Superapacitors (Adv. Electron. Mater. 2/2017). (February 2017) - Hou, Linrui; Bao, Ruiqi; Rehan, Muhammad; Tong, Liuniu; Pang, Gang; Zhang, Xiaogang; Yuan, Changzhou
Abstract : Uniform hollow mesoporous nickel cobalt sulfide micro‐dumbbells (NCS‐MDs) have been purposefully designed and utilized as a competitive electrode with exceptional gravimetric/volumetric pseudo‐capacitance for advanced electrochemical supercapacitors, as described by L. R. Hou in article number 1600322. Fascinating electrochemical features evidently highlight that their hollow mesoporous NCS‐MDs are a promising electrode platform for next‐generation hybrid supercapacitors.